Pemenuhan Syarat Minimum Dua Kreditur Dalam Proses Kepailitan Melalui Pembuktian Sederhana - Tiara Elpa Yuning Sari; Yahanan, Annalisa; Samawati, Putu (Lex Stricta : Jurnal Ilmu Hukum, 2025)
A bankruptcy petition is a legal step taken by creditors to demand repayment of debts if the debtor fails to fulfil their obligations. Simple proof in bankruptcy, especially regarding the existence of a second creditor, is often difficult to obtain. This study analyses how the two creditor requirements in bankruptcy petitions are met, as well as the legal consequences if these requirements are not met, which can lead to the rejection of the petition. The three decisions examined are Decision Number 30/Pdt.Sus.Pailit/2023/PN Niaga Jkt.Pst, Decision Number 15/Pdt.Sus. Pailit/2025/PN Niaga Jkt.Pst, and Decision Number 33/Pdt.Sus.Pailit/2020/PN Niaga Jkt.Pst. The method used is a normative approach with a legal case study. The results of the study show that simple proof does not mean without verification, but rather sufficient formal evidence showing two creditors. In two decisions, this requirement was proven, and the bankruptcy petition was accepted, while in one decision, the failure to prove the second creditor resulted in the petition being rejected. This study recommends improving bankruptcy law and creditors' understanding of the importance of simple proof to protect their receivables rights